ANALISIS VARIABILITAS CURAH HUJAN WILAYAH INDONESIA BERDASARKAN PENGAMATAN TAHUN 1975-2004 - Juaeni, Ina (MATEMATIKA, 2006)
Tropical rainfall is the most important  atmospheric  variable, because it can be  affect directly to human life.  Tropical rainfall is also important for global climate and weather.  The annual total of  tropical rainfall differs from year to year and from place to place. Other characteristics, such as its seasonal and diurnal distribution, intensity, and duration  also demonstrate spatial and temporal variations. Results of  the statistical analysis to rainfall data indicate that rainfall variation coefficients in the southern Indonesia are  higher than its in the northern Indonesia .